PENGEMBANGAN MEDIA PEMBELAJARAN FOTONOVELA BERBANTUAN AUDIO MATERI BUNYI UNTUK SISWA TUNARUNGU SMP LB/MTs LB (UPEJ Unnes Physics Education Journal, 2017)
The learning process of physics needed a deep analysis. Students with special needs, especially those who were deaf and lack in hearing ability, had some problems in Physics learning including in Sound concept. Availability of learning media in Physics learning for those deaf students was still in minimum number. There were deaf students who had hearing ability although it was less. The less hearing ability could still be employed to optimize the learning proces. This study aimed to develop fotonovela as a product of learning media with audio help for deaf students, and to determine the suitability and effectiveness of it. Result of the study concluded that the fotonovela with audio help was very suitably and effectively applied in the learning for deaf students.